Características demográficas, clínicas y esquemas de tratamiento de celulitis en pacientes pediátricos hospitalizados, Hospital Apoyo Iquitos, 2021 - 2022 - Cubas Osorio, Jessye (2023)
Cellulitis in pediatrics is one of the main reasons for consultation in primary care, for this reason adequate management and epidemiological study is crucial to prevent serious complications and reduce mortality. For this reason, the objective of this work is to identify the demographical, clinical characteristics and management schemes of cellulite in hospitalized pediatric patients, Hospital Apoyo Iquitos, 2021 - 2022. For this reason, a descriptive and cross-sectional study was developed, with 70 patien ts as a sample. pediatrics. Concluding that the majority of patients were aged 1 to < 2 years, came from urban areas (71.4%), had a hospitalization time of 3 to less than 7 days (64.3%), 50.0% and 38.6% of the cases were caused by a pre-existing skin infection and trauma respectively. It was also observed that cultures of the lesions were not performed in any case; all patients received intravenous treatment (100.0%). The most used therapeutic regimen consisted of Oxacillin (74.3%), in a lesser proportion combinations of antibiotics were observed, such as Oxacillin + Amikacin, Oxacillin + Clindamycin, Oxacillin + Ceftriaxone, Oxacillin + Gentamicin and Oxacillin + Ceftriaxone + Amikacin. The majority of patients received antibiotic therapy at the time of discharge (98.6%, with Dicloxacillin (52.2%), Amoxicillin/Clavulanic Acid (37.7%) and Cephalexin (10.1%) being the most commonly used.